Effect of Deposition Time on CIGS/TiO2 Solar Cell Fabrication Using PVD Sputtering Method - Hayati, SB. Widia Rezaly Biharu; Erdiansyah, Erdiansyah (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
The CIGS (Copper Indium Gallium Selenide) thin film solar cells have been widely studied for a long time and have achieved an important position in the photovoltaic (PV) market. CIGS is one of the most promising materials for thin film solar cell applications. In this study, a thin film synthesis process was carried out on an ITO (Indium Tin Oxide) substrate using CIGS and TiO2 (titanium Dioxide) with deposition time variations of 30. 45 and 60 minutes using the PVD DC (Physical Vapor Deposition Direct Current) Sputtering method. Based on the test results, there was a shift in the diffraction peak along with the addition of the TiO2 layer, which indicated that the crystallization of ITO began to decrease and the TiO2 peak began to appear at deposition times of 45 minutes and 60 minutes. The formation of polycrystalline indicates good crystallization and surface uniformity. The highest layer thickness was obtained at a deposition time of 60 minutes, which was 426 nm, due to the particle agglomeration process on the substrate surface. The larger the particle agglomerates formed, the thicker the layer on the substrate surface. The results of the UV-Vis (Ultraviolet Visible) spectrophotometer test also showed that the overall band gap energy value corresponds to the ideal value for photovoltaic thin films, namely in the range of 1.04 eV to 3.5 eV.